The Morpheme Class-Changing in Kurdish Language - Hamad, Sherwan H. (Humanities Journal of University of Zakho, 2018)
The research, which is entitled “the morpheme class-changing in Kurdish language”, attempts to define and analyze the phenomenon of morpheme class-changing in Kurdish language. The phenomenon is to alter and leave the word class for another which is done via the descriptive diachronic method. The paper is divided into two parts. In the first part, the phenomenon of class-changing was defined and its presence between both free and bound morphemes which are represented in the two morphological processes of affixicalization and debounding were attended. The second part is devoted to present the lexical and grammatical morphemes within the frame of both phenomena of lexicalization and grammaticalization providing sufficient example and evidence for both. At the end, the main conclusions, list of references and the research abstract in Arabic and English languages were presented.